Pathophysiology, histopathology and therapeutic of SARS-CoV-2 - Noman, Efaq; Al-Gheethi, Adel; Radin Mohamed, Radin Maya Saphira; Al-Shorgani, Najeeb; Talip, Balkis; Hezam, Kamal; Othman, Norzila (Penerbit UTHM, 2020)
The rapid transmission of SARS-CoV-2 through the world has induced the scientist to understand the histopathology of the virus and then to find an effective drug. However, many of the point associated with the virus pathogenicity still unknown and need more studies. In this chapter the pathophysiology, histopathology and therapeutic of SARS-CoV-2 has been reviewed. It was appeared that pathogenicity of SARS-CoV-2 is belonging to the viral with genome structure which acting by blocking the host innate immune response. Both chloroquine and hydroxyl-chloroquine have similar structure and mechanism action and they are among the most effective antiviral for treating the patents with the SARS-CoV-2. Chloroquine works by inhibition the intracellular organism by increasing the pH.